PENGARUH KARAKTERISTIK INDIVIDU DAN GAYA KEPEMIMPINAN TERHADAP KOMITMEN ORGANISASI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PERSONIL POLRES KOTA LHOKSEUMAWE - Zulfikar, Zulfikar; Marbawi, Marbawi; Aiyub, Aiyu (J-MIND (Jurnal Manajemen Indonesia), 2020)
ABSTRACT This study aims the influence of Individual Characteristc and transformational leadership on organizational commitment with job satisfaction as intervening variable to the Lhokseumawe police station. For the dependent variable of this study is individual characteristic and transformational leadership, the independent variable is the organizatioan commitment of the police station, Intervening variables are job satisfaction. The population in this study was the Police Personal of the Lhokseumawe District Police which numbered 575, the sampling technique used proportionate stratified random sampling and obtained a sample of 170 respondents who were police officers of the Lhokseumawe police station, the research method used is a quantitative method for data analysis method using Structural Equation Modeling (SEM). The results of this study indicate that, individual characteristic has a significant effect on job satisfaction, transformational leadership has a significant effect on job satisfaction, leadership has not a effect on organizational commitment, transformational leadership  has a significant effect on organization commitment, job satisfaction has a significant effect on organizational commitment, individual characteristic has not effect on organizational commitment through job satisfaction as an intervening variable, transformational leadership has a significant effect on organizational commitment through job satisfaction as an intervening variable. Keywords:     Individual Characteristic, Transformational Leadership, Job Satisfaction And Organizational Commitment.